Morphometric differences in central stress-regulating structures between women with and without borderline personality disorder - Kuhlmann, Andrea; Bertsch, Katja; Schmidinger, Ilinca; Thomann, Philipp; Herpertz, Sabine (Journal of psychiatry & neuroscience, 2013)
Background: Experiences of early life stress, increased psychological arousal and the body’s physiologic stress response seem to play an important role in the pathogenesis and maintenance of borderline personality disorder (BPD). In the present study, we investigated alterations in grey matter of central stress-regulating structures in female patients with BPD. Methods: We examined T1-weighted structural magnetic resonance imaging scans of unmedicated, right-handed female patients with BPD (according to DSM-IV criteria) and healthy controls matched for age, intelligence and education using fully automated DARTEL voxel-based morphometry. Our regions of interest analyses included the hippocampus, amygdala, anterior cingulate cortex (ACC) and hypothalamus. Results: We enrolled 30 patients and 33 controls in our study. The grey matter of patients with BPD was reduced in the hippocampus, but increased in the hypothalamus compared with healthy participants. Hypothalamic volume correlated positively with the history of traumatization in patients with BPD. No significant alterations were found in the amygdala and ACC. Limitations: This study is limited by the lack of measures of corticotropin-releasing hormone, adrenocorticotropic hormone and cortisol levels. Furthermore, moderate sample size and comorbid disorders need to be considered. Conclusion: Our findings provide new evidence for grey matter alterations in the hypothalamus and replicate previously reported decrements in hippocampal volume in patients with BPD. Understanding the role of the hypothalamus and other central stress-regulating structures could help us to further understand the neurobiological underpinnings of this complex disorder.
Accepted May 22, 2012
Gesehen am 29.06.2021